Wolność wypowiedzi : uwagi na tle regulacji europejskiej i amerykańskiej - Żukowski, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article deals with basic issues related to the protection of freedom of expression in Europe and the USA. The fundamental concepts of models for the admissibility of restrictions on the freedom of speech by states were discussed and characterized, and the characteristics of this freedom were discussed. The article also presents the historical background accompanying the development of freedom of expression in democratic countries.
Keywords: freedom of speech; freedom of expression; European Convention on Human Rights; First Amendment to the US Constitution; margin of appreciation